LOW ENERGY LASERS IN THE MANAGEMENT OF TRAUMATIC ULCERS IN ORAL MUCOSA - METHODS OF APPLICATION - Hristina Lalabonova (Peytchinski Publishing, 2014)
Introduction: Traumatic ulcers in the oral mucosa are extremely painful and can cause severe troubles in talking and eating. Their treatment can be quite prolonged. The present paper aimed at exploring the therapeutic potential of low energy laser irradiation (LELI) in treating oral mucosa traumatic ulcers and propose methods of stimulation of their healing using a laser with an appropriate wavelength and frequency of irradiation, appropriate dose and number of procedures. Material and methods: Thirty patients were recruited in the study. They were allocated into three groups: group 1 (a study group) - these patients received red laser irradiation with a wavelength of 658 nm; group 2 (a study group) - these had infrared laser irradiation with a wavelength of 904 nm; group 3 (a control group) - these patients were treated with granofurin and solcoseryl. With the technique we used the laser tip was placed at a distance from the irradiated area (0.5 cm2) with the fiber optic emitting in the red spectrum (658 nm) or the infra-red spectrum (904 nm). A diode laser was used in the study. We irradiated the area of the traumatic ulcer and the surrounding mucosa 0.5 to 1 cm in diameter. The applied dose was 1 - 2 J/cm2. The treatment procedure was repeated once daily until the symptoms disappeared. Results: We found that pain was rapidly managed with the treatment and epithelization of the ulcers was accelerated. Conclusions: LELI is an effective and easy-to-use modality to treat traumatic ulcers that obviates the use of drugs.